Pendidikan Ramah Anak sebagai Upaya Meningkatkan Solidaritas Sosial Siswa SMP Dwijendra Denpasar - Ermawati, Gusti Ayu Intan; Punia, I Nengah; Sastri Mahadewi, Ni Made Anggita (JURNAL ILMIAH SOSIOLOGI (SOROT), 2021)
Child-Friendly School (CFS) is a mandate that must be carried out by the nation to fulfill the rights of children as stated in the Convention on the Rights of the Child. SMP Dwijendra Denpasar is one of the SRA in Bali as well as at the national level. The approach used in this study is a qualitative approach with a descriptive-explanative research type. The theory used is the critical education paradigm of Paulo Freire to examine the application of child-friendly schools as an effort to increase the social solidarity of junior high school students Dwijendra Denpasar. In the future, the implementation of CFS is further improved by all school residents so that the implementation of CFS runs well. Keywords: Child-Friendly School, Social Solidarity, Student, SMP Dwijendra Denpasar